Homotopy Analysis Method for Fractional Reaction-Diffusion Equation with Ecological Parameters - MEHMOOD, Zaffar; MEHMOOD, Raja; YILDIRIM, Ahmet; MOHYUD-DIN, Syed Tauseef (Walailak Journal of Science and Technology (WJST), 2013)
This paper applies the Homotopy Analysis Method (HAM) to obtain analytical solutions of fractional reaction-diffusion equations with ecological parameters, which arise very frequently in mechanical engineering, control theory, solid mechanics and applied sciences. Numerical results reveal the complete compatibility of proposed algorithm for such problems. Some examples are presented to show the efficiency and simplicity of the method. doi:10.14456/WJST.2014.37